Sosialisasi Pencatatan Akuntansi Sederhana Pada UMKM Pengrajin Songket Desa Tanjung Laut Kabupaten Ogan Ilir - Mike Amelia; Septiani Fransisca (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Tanjung Laut Village, Tanjung Batu Sub-district, is a village where most of the population are Micro Small Medium Enterprise (MSME) craftsmen. The main problem faced by MSME in Tanjung Laut Village is limited knowledge about financial records. This socialisation aimed to improve the ability to record business finances and increase awareness that financial reports are very important for songket craftsmen in Tanjung Laut Village in developing their businesses. The methods used in this programme were observation, interviews and socialisation of simple financial records. The results of this activity are very useful for songket craftsmen in Tanjung Laut Village in understanding and doing simple financial records correctly, and starting to be interested in doing financial records